UDP-glucuronosyltransferases (UGTs) and their related metabolic cross-talk with internal homeostasis: A systematic review of UGT isoforms for precision medicine. (July 2017) - Yang, Na; Sun, Runbin; Liao, Xiaoying; Aa, Jiye; Wang, Guangji
Graphical abstract: Abstract: UDP-glucuronosyltransferases (UGTs) are the primary phase II enzymes catalyzing the conjugation of glucuronic acid to the xenobiotics with polar groups for facilitating their clearance. The UGTs belong to a superfamily that consists of diverse isoforms possessing distinct but overlapping metabolic activity. The abnormality or deficiency of UGTs in vivo is highly associated with some diseases, efficacy and toxicity of drugs, and precisely therapeutic personality. Despite the great effects and fruitful results achieved, to date, the expression and functions of individual UGTs have not been well clarified, the inconsistency of UGTs is often observed in human and experimental animals, and the complex regulation factors affecting UGTs have not been systematically summarized. This article gives an overview of updated reports on UGTs involving the various regulatory factors in terms of the genetic, environmental, pathological, and physiological effects on the functioning of individual UGTs, in turn, the dysfunction of UGTs induced disease risk and endo- or xenobiotic metabolism-related toxicity. The complex cross-talk effect of UGTs with internal homeostasis is systematically summarized and discussed in detail, which would be of great importance for personalized precision medicine.